Biting activity of Anopheles calderoni (Diptera: Culicidae) in two localities of Valle del Cauca, Colombia - LUCUMI-ARAGÓN, DIANA; GONZÁLEZ-O., RANULFO; SALAS-QUINCHUCUA, CRISTHIAN (Revista Colombiana de Entomología, 2011)
Anopheles calderoni has been recently registered in Colombia and apparently many bionomic aspects of An. punctimacula correspond to this species, to clarify this confusion is essential to develop prevention and control programs of malaria vectors, for that reason this paper evaluates its biting activity at three stations in two localities of Valle del Cauca, one in El Otoño (Candelaria) and two in Laguna de Sonso (Buga), 312 collecting hours were carried out with protected human bait in periods of 12 hours (18:00 to 06:00), 5.831 specimens were collected, 334 at El Otoño, 864 and 4.633 at Laguna de Sonso stations respectively. The biting rate per human per night (IPHN), the biting rate per human per hour (IPHH) and peak hours of biting activity varied among stations and sampling sites apparently related to the proximity of sampling stations to the breeding sites or to the availability and productivity of local breeding sites. The IPHN ranged from 26.5 to 78.5 (=55.7) in El Otoño, and between 16.5 and 157.0 (=65.8) and between 246.0 and 1265,5 (=661.9) in the station one and two respectively. In conclusion, at both localities the species showed unimodal and bimodal behavior depending on the densities and being heterogeneous between nights, which suggest a plasticity feature on its hematophagous behavior.